O silêncio na poesia de Orides Fontela e Alejandra Pizarnik - MORAES, Pedro Henrique Viana de (2022)
This research aims to understand how the phenomenon of silence is manifested in modern and contemporary poetry through the work of two poets, the Brazilian Orides Fontela (1949-1998) and the Argentinian Alejandra Pizarnik (1936-1972). To achieve this objective, the entire poetic work of both authors was analyzed to choose the poems that constituted the corpus. This research is divided into four chapters, the first of which analyzes the issue of silence as a phenomenon based on the ideas of Max Picard (1964), as well as reflections on how silence would poetically present itself. In this section, the theories of Bobes Naves (1992) Susan Sontag (2011), Kovadloff (2003), Mallarmé (2013), Octavio Paz (2012) and other authors are used. The second chapter deals with the study of the poems chosen by Orides Fontela, also bringing contributions from his critical fortune such as the analyzes of Alcides Villaça (1992,1996) and Alberto Pucheu (2019), in addition to relying on information from interviews, testimonials and biographical data. The third chapter addresses the work of the poet Alejandra Pizarnik and the understanding of her awareness of the limits of poetic expression. In this part, we have contributions from César Aira (2001), Patricia Venti (2007), Carolina Depetris (2000, 2004) and other theorists. Finally, the last chapter deals with the comparison between both authors regarding their points of approximation and divergence, based on the idea of comparatism described by Modesto Carone in his work A poética do silêncio (2000).